MULTIMEDIA E-LEARNING UNTUK MENUNJANG PEMBELAJARAN MATA KULIAH JARINGAN KOMPUTER DAN DATA DI UNIVERSITAS TELKOM - Indrarini Dyah Irawati; Leanna Vidya Yovita (Jurusan Teknik Informatika, 2014)
Computer and Data Networks is one of subject in Faculty of Electrical Engineering, Telkom University, that is still using the learning method by face-to-face between lecturer and students. The student’s problem is difficult to understand how computers and other communication devices can communicate each other, and in fact it is lack of visual aid. This paper presents multimedia e-learning that support for studying about Communication Protocol and IPv4 modules. E-learning multimedia content created in the form of video tutorials and animation using flash. In modules are also equipped with exercises to explore student’s understanding. Analysis shows that the e-learning modules provide added value to the students to increase their knowledge and improve the number of graduation.